The International Monetary Fund in a Time of Crisis: A Review of Stanley Fischer'sIMF Essays from a Time of Crisis: The International Financial System, Stabilization, and Development - Conway, Patrick (Journal of Economic Literature, 2006)
Stanley Fischer was deputy managing director of the IMF from 1994 to 2001 and, perhaps more than any other individual, he personifies the international “rapid response” to financial crises in the 1990s. This book is a collection of essays written during his tenure at the IMF; taken together, the essays represent the strongest and most logical defense of IMF initiatives in the 1990s in print. My review essay comprises six parts. In parts 2 through 4, I provide an overview of Fischer's arguments in three central areas of contention: stabilization policy, the impact of IMF programs on poverty, and the IMF's anticipation of and response to international financial crisis. I then compare Fischer's arguments to those raised by the IMF's critics during that period. The controversial issues of these parts can be resolved only through empirical investigation but, on the issues of greatest importance from the financial crises of the 1990s, both Fischer and the IMF's critics make logically consistent arguments with little empirical support. In part 5, I review the recent empirical literature to illuminate what evidence has been found in support of—or counter to—the assertions of Fischer and the IMF's critics. Part 6 provides conclusions and suggestions for follow-on empirical research.